Improving Poetry Writing Skills Using Image Media Among Grade X Science Students at MA Al-Ikhlas Kairatu - Indra Yani; Petrus Jacob Pattiasina; Viona Sapulette (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aimed to determine the improvement in poetry writing skills through the use of image media among Grade X Science students at MA Al-Ikhlas Kairatu, Waitasi Hamlet, West Seram Regency. The sample consisted of 16 students. Data collection techniques were carried out using test instruments consisting of observation, interviews, assignments, questionnaires, and documentation. The improvement in poetry writing skills was observed through two cycles. In Cycle I, the results were not optimal, as 8 students did not meet the Minimum Mastery Criteria (MMC), while only 8 students achieved the required standard. In contrast, Cycle II showed effective learning outcomes, where all 16 students successfully met the MMC. These findings indicate the students’ success in participating in the learning process. Based on the results of the study, it can be concluded that the use of image media improved the poetry writing skills of Grade X Science students at MA Al-Ikhlas Kairatu. The researchers suggest that the use of image media in Indonesian language learning, especially in poetry writing, can provide valuable input for teachers in encouraging students to improve their poetry writing skills optimally.